Evaluation of modeled land‐atmosphere exchanges with a comprehensive water isotope fractionation scheme in version 4 of the Community Land Model. (28th April 2017) - Wong, Tony E.; Nusbaumer, Jesse; Noone, David C.
Abstract: All physical process models and field observations are inherently imperfect, so there is a need to both (1) obtain measurements capable of constraining quantities of interest and (2) develop frameworks for assessment in which the desired processes and their uncertainties may be characterized. Incorporation of stable water isotopes into land surface schemes offers a complimentary approach to constrain hydrological processes such as evapotranspiration, and yields acute insight into the hydrological and biogeochemical behaviors of the domain. Here a stable water isotopic scheme in the National Center for Atmospheric Research's version 4 of the Community Land Model (CLM4) is presented. An overview of the isotopic methods is given. Isotopic model results are compared to available data sets on site‐level and global scales for validation. Comparisons of site‐level soil moisture and isotope ratios reveal that surface water does not percolate as deeply into the soil as observed in field measurements. The broad success of the new model provides confidence in its use for a range of climate and hydrological studies, while the sensitivity of simulation results to kinetic processes stands as a reminder that new theoretical development and refinement of kinetic effect parameterizations is needed to achieve further improvements. Key Points: Water isotope physics have been added to the version 4 of the Community Land Model An imperfect soil moisture simulation has limited impacts on soil water isotopic profiles Soil evaporative kinetic effect alone cannot rectify coupled model discrepancy with respect to water isotopic data